Does CLIL shape language attitudes and motivation? Interactions with target languages and instruction levels. Issue 5 (28th May 2023) - De Smet, Audrey; Mettewie, Laurence; Hiligsmann, Philippe; Galand, Benoît; Van Mensel, Luk
ABSTRACT: Besides being promoted as a way to improve target language proficiency, Content and Language Integrated Learning (CLIL) is also believed to positively impact socio-affective variables such as language attitudes and motivation. Yet, few extensive empirical studies exist on these aspects in CLIL. The present contribution aims to address this gap in the literature by investigating language attitudes and motivation in CLIL on a large scale across two target languages (English and Dutch) and two instruction levels (primary and secondary). Questionnaire data were collected from 896 pupils in French-speaking Belgium measuring their language attitudes in terms of perceived easiness and attractiveness of the target language and their motivation in terms of expectancy for success, task value and cost. Results of the MANCOVAs show pupils report more positive attitudes and higher motivation in CLIL compared to non-CLIL and in English compared to Dutch. However, these differences mainly appear at secondary level, suggesting more favorable profiles develop after the fifth grade, which is the onset of formal foreign language instruction for non-CLIL pupils. Moreover, the effect sizes indicate that the target language (English vs. Dutch) plays a more crucial role than CLIL vs. non-CLIL regarding language attitudes and motivation.